2013
DOI: 10.1074/jbc.m113.450239
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Lectin Mannose 6-Phosphate Receptor Homology (MRH) Domain of Glucosidase II, an Enzyme That Regulates Glycoprotein Folding Quality Control in the Endoplasmic Reticulum

Abstract: Background: Glucosidase II is an endoplasmic reticulum enzyme involved in quality control of glycoprotein folding. Results: The structure of the lectin domain of GII was determined by NMR spectroscopy. Conclusion: GII lectin domain structure contains a unique Trp residue critical for GII activity. Significance: GII␤ MRH domain structure is the first determined of an MRH domain present in a protein with enzymatic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 53 publications
1
55
1
Order By: Relevance
“…Mutation of W409 decreased the efficiency of GII’s removal of glucose residues from G2M9 and G1M9 both in vivo and in vitro , although not to the extent observed for GII harboring a mutation of either glutamate or tyrosine in the primary mannose binding pocket. 18,33 However, contrary to the mutations within the primary mannose binding pocket, we observed that the W409A mutant was still able to bind Man α 1,2Man as monitored by 15 N– 1 H HSQC and surface plasmon resonance analyses using the lysosomal enzyme acid α -glucosidase. To further investigate the mechanism by which GII β binds glycans to enhance the catalytic activity of GII, structural studies of wild-type and mutant forms of the MRH domain of GII β subunit were performed and evaluated by in vitro and in vivo GII activity assays.…”
contrasting
confidence: 58%
See 4 more Smart Citations
“…Mutation of W409 decreased the efficiency of GII’s removal of glucose residues from G2M9 and G1M9 both in vivo and in vitro , although not to the extent observed for GII harboring a mutation of either glutamate or tyrosine in the primary mannose binding pocket. 18,33 However, contrary to the mutations within the primary mannose binding pocket, we observed that the W409A mutant was still able to bind Man α 1,2Man as monitored by 15 N– 1 H HSQC and surface plasmon resonance analyses using the lysosomal enzyme acid α -glucosidase. To further investigate the mechanism by which GII β binds glycans to enhance the catalytic activity of GII, structural studies of wild-type and mutant forms of the MRH domain of GII β subunit were performed and evaluated by in vitro and in vivo GII activity assays.…”
contrasting
confidence: 58%
“…These constructs (pREP1-GII β Y372A and pREP1-GII β Y372F) were then electroporated into S. pombe competent Δ GIIβ cells. The pREP1-GII β W409A construct used in this study was described by Olson et al, 33 and the wild-type and MRH binding pocket mutant construct used in this study (pREP1-GII β and pREP1-GII β Y439F, respectively) were described by Stigliano et al (please note that the numbering of this last mutant was changed from Y462F used in ref 18 as throughout this work the numbering corresponds to the mature protein sequence instead of starting at the initial Met).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations